2006
DOI: 10.1055/s-2006-924966
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide Increases Thyroid Radiosensitivity by Stimulating Nitric Oxide Synthase Expression and the Generation of Organic Peroxides

Abstract: Differentiated thyroid cancer and hyperthyroidism are treated with radioiodine. However, when the radioisotope dose exceeds certain limits, the patient must be hospitalized to avoid contact with people that would otherwise be exposed to radiation. It would be desirable to obtain a similar therapeutic effect using lower radioiodine doses. Radiosensitizers can be utilized for this purpose. Nicotinamide (NA) increases thyroid radiosensitivity to 131I in both normal and goitrous glands. NA causes a significant inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 17 publications
0
7
0
1
Order By: Relevance
“…It has been previously shown that nicotinamide inhibits the inducible NOS enzyme activity in macrophages, allowing NO to inhibit its own formation 25 . There are recent reports showing that nicotinamide increases endogenous NOS, which would in turn stimulate NO production, increasing thyroid blood flow 26 . It is unlikely however, that any NO‐mediated actions of the agents studied were dependent on DNA synthesis in our study because of the short time‐frame.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…It has been previously shown that nicotinamide inhibits the inducible NOS enzyme activity in macrophages, allowing NO to inhibit its own formation 25 . There are recent reports showing that nicotinamide increases endogenous NOS, which would in turn stimulate NO production, increasing thyroid blood flow 26 . It is unlikely however, that any NO‐mediated actions of the agents studied were dependent on DNA synthesis in our study because of the short time‐frame.…”
Section: Discussionmentioning
confidence: 72%
“…25 There are recent reports showing that nicotinamide increases endogenous NOS, which would in turn stimulate NO production, increasing thyroid blood flow. 26 It is unlikely however, that any NOmediated actions of the agents studied were dependent on DNA synthesis in our study because of the short time-frame. As nicotinamide possesses antioxidant properties, 27 it might be related instead to the enhancement of NO bioavailability.…”
Section: Discussionmentioning
confidence: 80%
“…It is a guanidine-substituted analogue of L-arginine and acts as a potent endogenous competitive inhibitor of all isoforms of nitric oxide synthase (NOS): neuronal (n) NOS, inducible (i) NOS, and endothelial (e) NOS [23,24] . Nitric oxide (NO), the most widely studied endothelium-derived molecule, exerts potent vasodilatory, antiplatelet, anti-infl ammatory, antiproliferative / antitumor and antioxidant eff ects [25] . Because of these functions, NO has been characterized as an endogenous anti-atherosclerotic molecule [26] .…”
Section: Nitric Oxide Endothelial Function and Insulin Resistancementioning
confidence: 99%
“…В условиях in vitro никотинамид выраженно снижал продукцию NO в культуре эндокринных клеток поджелудочной железы человека или мышиных макрофагов частично восстанавливая инсулиновую функцию клеток железы [130]. Однако у крыс никотинамид по вышает радиочувствительность щитовидной железы к йоду-131 за счет усиления экспрессии eNOS, увеличения кровотока и повреждения ткани органическими пероксидами [131].…”
Section: обзорные статьиunclassified